1157 WITCHING FROM DUAL ANTIPLATELET THERAPY WITH ASPIRIN PLUS A P2Y12 INHIBITOR TO DUAL PATHWAY INHIBITION WITH ASPIRIN PLUS VASCULAR-DOSE RIVAROXABAN: THE SWITCHING ANTI-PLATELET AND ANTI-COAGULANT THERAPY (SWAP-AC) STUDY. (15th December 2022) - Giordano, Salvatore; Ortega-paz, Luis; Franchi, Francesco; Rollini, Fabiana; Galli, Mattia; Been, Latonya; Ghanem, Ghussan; Shalhoub, Awss; Ossi, Tiffany; Rivas, Andrea; Zhou, Xuan; Pineda, Andres M.; et al.
Abstract: Aims: To assess the feasibility of switching from dual antiplatelet therapy (DAPT) to dual pathway inhibition (DPI) and to compare the pharmacodynamic (PD) profiles of these treatment regimens. Methods and results: This was a prospective, randomized, PD study conducted in 90 patients with chronic coronary syndrome (CCS) on DAPT with aspirin (81 mg/qd) plus a P2Y12 inhibitor [clopidogrel (75 mg/qd; n = 30), ticagrelor (90 mg/bid; n = 30), or prasugrel (10 mg/qd; n = 30)]. Patients in each cohort were randomized to maintain DAPT or switch to DPI (aspirin 81 mg/qd plus rivaroxaban 2.5 mg/bid). PD assessments included: VerifyNow P2Y12 reaction units; light transmittance aggregometry following stimuli with adenosine diphosphate (ADP), tissue factor, and a combination of collagen, ADP, and TF (CATF, maximum platelet aggregation %); thrombelastograph coagulation analyzer; thrombin generation (TG). Assays were performed at baseline (on DAPT) and 30 days post-randomization (trough and peak). Switching from DAPT to DPI occurred without major side effects. DAPT was associated with enhanced P2Y12 inhibition, while DPI with reduced TG. Platelet-mediated global thrombogenicity (primary endpoint) showed no differences between DAPT and DPI in the ticagrelor (14.5% [0.0–63.0] vs. 20.0% [0.0–70.0]; p = 0.477) and prasugrel (20.0% [0.0–66.0] vs. 4.0% [0.0–70.0]; p = 0.482), but not clopidogrel (27.0% [0.0–68.0] vs. 53.0% [0.0–81.0]; p = 0.011), cohorts. Conclusion: In patients with CCS, switching from different DAPT regimens to DPI was feasible, showing enhanced P2Y12 inhibition with DAPT and reduced TG with DPI, with no differences in platelet-mediated global thrombogenicity between DPI and ticagrelor- and prasugrel, but not clopidogrel-, based DAPT.